2006
DOI: 10.1093/pcp/pcj064
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Rice Cryptochromes in De-etiolation Responses and Flowering

Abstract: In order to elucidate the function of cryptochromes (cry) in rice, we have characterized all rice CRY genes, including OsCRY1a, OsCRY1b and OsCRY2. Our studies revealed that OsCRY1 genes were mainly expressed in the green plant tissue, while OsCRY2 gene expression was high in the coleoptile, flower and callus. Light treatment affected neither the expression of any of the OsCRY genes nor the stability of their transcripts. However, it was found that Oscry2 protein was negatively regulated by blue light. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
65
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 44 publications
0
65
0
Order By: Relevance
“…Tomato (Solanum lycopersicum, formerly Lycopersicon esculentum) possesses two CRY1 subfamily members, LeCRY1a and LeCRY1b (Perrotta et al, 2000(Perrotta et al, , 2001, and garden pea (Pisum sativum) contains two CRY2 subfamily members, PsCRY2a and PsCRY2b (Platten et al, 2005). The monocot rice (Oryza sativa) has four CRY genes: OsCRY1a, OsCRY1b, OsCRY2, and OsCRY-DASH (Hirose et al, 2006;Zhang et al, 2006). The N-and C-terminal domains of OsCRY1a and OsCRY1b are 7% and 19% different, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tomato (Solanum lycopersicum, formerly Lycopersicon esculentum) possesses two CRY1 subfamily members, LeCRY1a and LeCRY1b (Perrotta et al, 2000(Perrotta et al, , 2001, and garden pea (Pisum sativum) contains two CRY2 subfamily members, PsCRY2a and PsCRY2b (Platten et al, 2005). The monocot rice (Oryza sativa) has four CRY genes: OsCRY1a, OsCRY1b, OsCRY2, and OsCRY-DASH (Hirose et al, 2006;Zhang et al, 2006). The N-and C-terminal domains of OsCRY1a and OsCRY1b are 7% and 19% different, respectively.…”
mentioning
confidence: 99%
“…Hirose et al (2006) showed that overexpression of OsCRY1 resulted in enhanced responsiveness to blue light, suggesting that OsCRY1 is similar to AtCRY1 in regulating photomorphogenesis. Like AtCRY2, OsCRY2 is involved in the promotion of flowering time in rice (Hirose et al, 2006). Barley (Hordeum vulgare) might have the same CRY gene composition as rice (Perrotta et al, 2001).…”
mentioning
confidence: 99%
“…[6][7][8] This indicates conserved CRY signaling in monocots and dicots. However, the underlying mechanisms may not be identical.…”
mentioning
confidence: 88%
“…In rice, three cryptochromes, OsCRY1a, OsCRY1b and OsCRY2, have been identified and only the latter is involved in the promotion of flowering time (Hirose et al, 2006). In tomato, overexpression or silencing of CRY2 had no effect on the developmental timing of the transition to flowering, although the rate of leaf production was altered causing a delayed appearance of flowers (Giliberto et al, 2005).…”
Section: Blue Light Receptorsmentioning
confidence: 99%